Beban Kerja Perawat Pelaksana Berdasarkan Metode Workload Indicator Staff Need (WISN) - Yeni Susilawati; Maria Komariah; Irman Somantri (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the workload of implementing nurses based on the WISN method. The method used is quantitative with work sampling and observation techniques. The results showed that the percentage of implementing direct nursing activities was 32.2% and indirect nursing activities was 34.4%. The proportion of time obtained from the workload component of direct and indirect activities is still within the light workload limit of 66.6%. In conclusion, nurses must increase productive activities by focusing on their primary tasks and functions, especially meeting basic human needs (KDM). Keywords: Workload, Nurses, WISN, Work Sampling